Behavior of seeking counseling assistance among middle school students (Journal of the College of Basic Education, 2022)
The current research aims to identify the level of behavior of requesting counseling assistance among middle school students, and the research is limited to middle school students in the first Rusafa Directorates of Education in Baghdad Governorate for the academic year 2021/2022. The (Ibrahim 2021) scale, and after processing the data in the SSPS statistical portfolio, the research reached the most important results, the most important of which is that the level of behavior of counseling assistance request for middle school students was weak, and the research came out with a set of recommendations and suggestions.